Synchronous discussion in online learning: Investigating students’ critical thinking - Prilla Lukis Wediyantoro; Malikhatul Lailiyah; Karlina Karadila Yustisia (Universitas Merdeka Malang, 2020)
Many studies mentioned the importance of fostering higher education students’ critical thinking skills in order to prepare them for their future career. However, many scholars contend that in online courses, critical thinking is difficult to accomplish. Understanding this gap, this paper aims to report the using of Socratic Questions strategy on synchronous discussion as the bridge to promote students’ critical thinking in online learning environment. Twenty two Diploma 3 students who were enrolled in Intermediate Reading course, participated in this study. Due to the spread of Covid-19 pandemic, this class was switched into online learning. To gather the data, the content of participants’ individual post will be analysed to know the depth of students’ critical thinking based on Yang et al.’s (2005) model. In addition, both quantitative and qualitative analysis of students’ post will be applied to measure the effects of Socratic questioning on students’ critical thinking in synchronous discussion in online learning. The result revealed that Socratic questions strategy were successfully improve students’ depth of critical thinking. DOI: 10.26905/enjourme.v5i2.5205